2018
DOI: 10.1016/j.cmet.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Breast Cancer Stem Cell State Equilibrium through Modulation of Redox Signaling

Abstract: Although breast cancer stem cells (BCSCs) display plasticity transitioning between quiescent mesenchymal-like (M) and proliferative epithelial-like (E) states, how this plasticity is regulated by metabolic or oxidative stress remains poorly understood. Here, we show that M- and E-BCSCs rely on distinct metabolic pathways and display markedly different sensitivities to inhibitors of glycolysis and redox metabolism. Metabolic or oxidative stress generated by 2DG, HO, or hypoxia promotes the transition of ROS M-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
276
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(286 citation statements)
references
References 55 publications
10
276
0
Order By: Relevance
“…Reinforcing these predictions, NRF2 has been related to cancer stem-like traits and chemo-resistance [35]. Remarkably, a recent study reported a strong NRF2-mediated antioxidant response in hybrid E/M-like breast cancer stem cells (BCSC), and a significant association of NRF2 with poor prognosis [46]. These experimental observations resonate well with the worse clinical outcome and an association of a hybrid E/M phenotype with high NRF2 expression, and support the increasingly accepted notion that a hybrid E/M phenotype, rather than a completely mesenchymal one, may correlate with a higher metastatic potential [1].…”
Section: Discussionmentioning
confidence: 75%
“…Reinforcing these predictions, NRF2 has been related to cancer stem-like traits and chemo-resistance [35]. Remarkably, a recent study reported a strong NRF2-mediated antioxidant response in hybrid E/M-like breast cancer stem cells (BCSC), and a significant association of NRF2 with poor prognosis [46]. These experimental observations resonate well with the worse clinical outcome and an association of a hybrid E/M phenotype with high NRF2 expression, and support the increasingly accepted notion that a hybrid E/M phenotype, rather than a completely mesenchymal one, may correlate with a higher metastatic potential [1].…”
Section: Discussionmentioning
confidence: 75%
“…In addition, we have previously shown that platinum-based drugs readily induce EMT phenomenon in OC cells [76,78]. A recent study on breast cancer stem cells (BCSCs) demonstrated that metabolic and oxidative stress transitions the ROS low mesenchymal BCSCs to a ROS high epithelial state [250]. The increased response of carboplatin-resistant OV90 cell line to BT#9 compared to parental control is under investigation.…”
Section: Role Of Magmas Inhibitor In Ovarian Cancer Treatmentmentioning
confidence: 99%
“…We used FLIM to quantify metabolic differences between wildtype and PAI1 cells based on endogenous fluorescence from NADH as described previously (ISS FastFLIM; refs. 19,20). For both NADH and mCherry, we used 740 nm excitation, 25 Â NIR corrected objective, 512 Â 512 matrix, 15% laser power, 4 ms dwell time, and 2.5Â electronic zoom (Olympus FVMPE-RS upright microscope with Spectra-Physics Insight DSþ laser).…”
Section: Flim and Metabolic Analysismentioning
confidence: 99%